Analyzing the Implications of Tax Accounting Rules on Capitalization and Expense Treatment - Safitri, Lina (Advances in Taxation Research, 2023)
Purpose: This study aims to investigate the implications of tax accounting rules for businesses, stakeholders, and regulatory bodies regarding the treatment of capitalization and expenses. Research Design and Methodology: This research uses a qualitative approach based on a literature review by collecting, analyzing, and interpreting existing scholarly works to develop a comprehensive understanding of the topic. Findings and Discussion: The findings of this study indicate the significant complexities and challenges businesses face due to mismatches between financial accounting practices and tax reporting, which affect the assessment of economic performance and stakeholder perceptions. These mismatches create barriers to company valuation, shareholder wealth creation, and market efficiency. Implications: This study emphasizes the need for improved tax governance mechanisms, longitudinal analysis of regulatory changes, comparative studies across industries and jurisdictions, and cross-disciplinary research to deepen understanding of the socio-economic implications of tax regulation. This research contributes to creating a more effective, equitable tax system that supports economic growth and social welfare.